Libertinos, tolerância religiosa e inquisição sob o reformismo ilustrado luso-brasileiro: formulações, difusão e representações (1756- 1807) - Igor Tadeu Camilo Rocha (2015)
This study sought to investigate the formulation, ideas and representations of religious tolerance under the Enlightened Reformism in luso-brazilian world, with the general hypothesis that the institutional reforms touching the Inquisition, Catholic Church and regular and secular catholic clergy created, albeit indirectly, conditions for a defense of religious tolerance was diffused more widely. The research, at first, started from a historiographical discussion on the theme of religious tolerance among its "appearance" in the Early Modern Age until the Enlightenment period, the proposed period. The objective was to think of it as a historical object of reflection and disputes between different interpretations, and to present possible particulars of their study in the lusobrazilian context. Focusing between the second half of the eighteenth century and the first decade of the nineteenth, this dissertation focused on the analysis of the defense of religious tolerance contained in the statements of those names libertines who fell in the meshes of the Portuguese Inquisition, in a context of broad institutional changes in Portugal and its colonies. With the understanding that religious tolerance was a heterodox matter within a reality marked by a unity project between the kingdom of Portugal and the Catholic Church, we analyzed the inquisitorial sources in order to discuss the extent to the heretical propositions in defense of religious tolerance were formulated and disseminated in this context. In these propositions, some approaches were observed on this research between religious conceptions that refer to a popular religiosity with conceptions of religious tolerance in according to an Enlightenments source.